THE IMPACT OF POLLUTION ON HYPERTENSION AND ECONOMY. (June 2022) - De Rosa, Maria Leonarda; Zuccarino, Marta; Di Sarro, Elena; Iovino, Miriam Dafne; Spoleto, Mariorosario; Ferrara, Nicola
Abstract : Objective: We investigated whether traffic-related air pollution and noise are associated with incident hypertension in Naples, Italy, our city. Given the pervasive nature and significant health effects of environmental noise pollution, the corresponding economic impacts may be substantial. Design and method: We included 102 study our ambulatory patients for air pollution effects. The economic assessment developed a new approach to estimate the impact of environmental noise on the prevalence and cost of key components of hypertension. Noise data our exposure estimates were derived from are > 30 years old. We modelled concentrations of particulate matter with aerodynamic diameter < = 2, 5 microm, PM2.5, < = 10microm, PM 10, > 2, 5, and < = 10microm, PM coarse, soot, PM2.5 absorbance, and nitrogen oxides at the addresses of participants with land use regression. Residential exposure to traffic noise was modelled in according to the EU Directive 2002 /49 / EC.We assessed hypertension as self-reported and measured (systolic blood pressure = > 140 mmHg or diastolic BP = > 90 mmHg or intake of antihypertensive drugs We used Poisson regression to analyze associations of traffic-related exposures with incidence of hypertension, controlling for relevant confounders. Results: Among 102 participants free of self-reported hypertension at baseline, 11 incident cases occurred within 1–3 years of follow-up. Incidence of self-reported hypertension was positively associated with PM2.5 relative risk 1.22[95%-confidence interval:1.08; 1.37] per 5 microg/m³) and PM2.5 absorbance (relative risk 1.13[95%CI:1.02; 1.24] .These estimates decreased slightly upon adjustment for road traffic noise. Road traffic noise was weakly positively associated with the incidence of self-reported hypertension. Among 102 participants at risk, 34 new cases of measured hypertension occurred. We found no clear associations with measured hypertension. The analyses suggested that a 5-dB noise reduction scenario would reduce the Hypertension prevalence by 1.4% Conclusions: Long-term residential exposures to air pollution and noise are associated with increased incidence of self-reported hypertension. These findings suggest significant economic impacts from environmental noise-related cardiovascular disease. Given these initial findings, noise may deserve increased priority and research as an environmental health hazard.